2015
DOI: 10.1071/rj15012
|View full text |Cite
|
Sign up to set email alerts
|

Improved grazing management practices in the catchments of the Great Barrier Reef, Australia: does climate variability influence their adoption by landholders?

Abstract: The declining health of the Great Barrier Reef from diffuse source pollutants has resulted in substantial policy attention on increasing the adoption of improved management practices by agricultural producers. Although economic modelling indicates that many improved management practices are financially rewarding, landholders with dated management practices remain hesitant to change. This research involved bio-economic modelling to understand the variance in private returns for grazing enterprises across a clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…as described by Thorburn & Wilkinson ()) required to reduce land‐based pollution is a substantial socio‐economic challenge (Thorburn et al ., ; Van Grieken et al ., ; Rolfe & Gregg, ). A considerable body of research suggests that landholders who adopt BMPs that maintain their pastures in better condition or apply fertilizer and pesticides at reduced rates are likely to generate better financial returns (Ash et al ., ; O'reagain et al ., ; Van Grieken et al ., ; Star et al ., ). However, several factors may lead to farmers deciding not to consider the adoption of BMPs into their business.…”
Section: Achieving the Reef Plan Goal And Targets For Reduction In Lamentioning
confidence: 99%
See 2 more Smart Citations
“…as described by Thorburn & Wilkinson ()) required to reduce land‐based pollution is a substantial socio‐economic challenge (Thorburn et al ., ; Van Grieken et al ., ; Rolfe & Gregg, ). A considerable body of research suggests that landholders who adopt BMPs that maintain their pastures in better condition or apply fertilizer and pesticides at reduced rates are likely to generate better financial returns (Ash et al ., ; O'reagain et al ., ; Van Grieken et al ., ; Star et al ., ). However, several factors may lead to farmers deciding not to consider the adoption of BMPs into their business.…”
Section: Achieving the Reef Plan Goal And Targets For Reduction In Lamentioning
confidence: 99%
“…However, several factors may lead to farmers deciding not to consider the adoption of BMPs into their business. In grazing lands, seasonal economic drivers such as low cash flow commonly experienced by graziers during droughts may encourage overgrazing and reduced ground cover during droughts Star et al, 2015). In sugarcane, aiming to achieve maximum yield to increase sugar mill profitability may encourage overapplication of fertilizers and pesticides (Van Grieken et al, 2013a).…”
Section: The Reef Water Quality Protection Planmentioning
confidence: 99%
See 1 more Smart Citation
“…The costs highlighted the heterogeneity between locations, land types and the importance of climate sequences (Rolfe and Windle, 2016). Following this more catchment scale costings across adoption of a suite of practices was explored with the outcomes of land condition used as the proxy for land management, and many of the paddock scale outcomes extrapolated to catchments (Star et al, 2015b).…”
Section: Overview Of Optimisation Approachesmentioning
confidence: 99%
“…Studies have shown that the vast majority of sediment is generated by over‐stocking and poor grazing land management that also reduce resource quality (Star et al . , ). Behaviours in these contexts may be driven by a complex set of factors, but recent work indicates that bounded rationality and behavioural aspects may be important (Rolfe and Gregg ).…”
Section: Introductionmentioning
confidence: 99%